Periodization of formation process of Ukrainian maritime legislation in conditions of its bringing to the international maritime law standards - Rebkalo, Mykola (Actual problems of law (Aktual’ni problemi pravoznavstva), 2019)
The article proposes an author’s view on the need for periodization of the maritime legislation of Ukraine in the process of bringing it into international maritime standards. In the course of the study the characteristic features, which are inherent to each specified stage and formulated certain conclusions in this regard were conducted in the article. The time interval during which the study was conducted, the author conditionally divided into three stages. In the course of the characteristics of each identified stage, the main organizational and legal measures by various levels of government were analyzed. It is established that the first stage was characterized by the creation of a normative base on the basis of such principles as universality, democracy, anti-discrimination. At the second stage, the formation process of Ukrainian maritime law was marked by the factors: creation of the bill, which laid the essential provisions of major international maritime acts; the program of international law adaptation into the Ukrainian legislation were created and implemented; Ukraine has received its own jurisprudence regarding the resolution of international maritime disputes. The third stage is characterized by activation of activities of the Verkhovna Rada of Ukraine, executive bodies for the implementation of the Ukrainian maritime legislation of international norms and their application in order to regulate the territorial sea exploitation, coastal structures, sea vessels and the implementation of maritime security measures. The article formulates the conclusions in which the author summarized the following: specificity of Ukraine’s implementation of international maritime law norms is to recognize the mechanism of governing the international community’s relations on the World Ocean; Ukraine has taken an inevitable course towards the implementation of international maritime standards in the current legislation; It is noted that the legislative work and practice of law enforcement bodies of all state power branches is essential for the formation process of the Ukrainian maritime legislation, but it has not yet acquired the appearance of a consistent system; in the course of implementing measures to update the Ukrainian maritime legislation, the President’s participation is minimized. The author believes the proposed periodization to serve for systematization of the Ukrainian maritime legislation in the future.